ChemInform Abstract: Sequential Mukaiyama—Michael Reaction Induced by Carbon Acids. Issue 26 (June 2016) - Yanai, Hikaru; Kobayashi, Osamu; Takada, Kenji; Isono, Takuya; Satoh, Toshifumi; Matsumoto, Takashi
Abstract: A strong C—H acidic compound (TCA) is described as catalyst for the sequential Mukaiyama—Michael aldol reaction of α‐pyrone derivatives with the silyl ketene acetal (II) and ketones or different α, β‐unsaturated ketones.